Facing the Data Analysis Complexity for the Energetic Efficiency Management at Great Copper Mining, in Codelco Chuquicamata, Chile [Enfrentando la Complejidad de Análisis de Datos Para la Gestión de la Eficiencia Energética en la Gran Minería del Cobre, en Codelco Chuquicamata, Chile] - Carrasco-Armijo, R; Fuertes-Sanchez, G (Institute of Electrical and Electronics Engineers Inc., 2016)
This study is centered in the complexity of the data analysis for the management of the energetic efficiency in the productive processes of copper. For that the study is divided in two stages, in the first one, through a process of hierarchical analysis (AHP), it is stablished the importance of the characteristics to be considered for the gathering of information related to the energetic efficiency. In the second stage, it is analyzed how the energetic consumption results a critical variable in copper production, being the unitarian operation of the concentrator, the one of the most energetic consumption, together with its most important actives, the SAG and Ball mills. Consequently, the study standarized a model to obtain data in the concentrator, thus evaluate the different areas of the organization, according to the characteristics or qualities of the information. © 2016 IEEE.